Eksplorasi Airtanah untuk Mengetahui Letak dan Sebaran Akuifer dengan Menggunakan Metode Geolistrik di Desa Kertasari dan Meraran, Kec. Taliwang, Kabupaten Sumbawa Besar - Roh Santoso Budi Waspodo (PERTETA, 2018)
AbstractDevelopment in water resource is an effort to give water access equitably to the community. Profound study of geology – hydrogeology analysis for springwater and groundwater which will be used to support various activity in society is required. The intention of this geo-electric study was to understand the hydrogeological conditions through aquifer distribution characteristic based on rock resistivity in Kertasari and Meraran Village, Taliwang Sub-district, Sumbawa Besar District. The goal of this study was to provide fundamental data of groundwater resource for seaweed industry needs in Kertasari and Meraran Village, Taliwang Sub-district, Sumbawa Besar District. Kertasari village located at coordinate 116⁰ 47' 20.9